Paint in Comfort in ANY Weather - Dow Chemical Company (1953)
Print advertisement for Dow Latex Paints, a fast-drying and durable interior wall paint manufactured by the Dow Chemical Company. The advertisement features a woman applying paint to a wall with a roller, while a man in the background hangs a painting. An inset illustration, styled as a film strip, shows the woman washing paint off of the roller. The accompanying text describes the qualities of latex paints. This advertisement appeared on page 321 of the October 1953 edition of Better Homes & Gardens.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Latex paint; Interior painting; Women in advertising